The correlation between intensive care unit attending physician continuity of care with financial and clinical outcomes. Issue 4 (25th May 2018) - Selvam, Pooja V.; Furqan, Muhammad M.; York, Sarah; Vaidya, Dhananjay; Hoang, Etter; Trost, Jeffrey C.; Williams, Marlene S.; Chandra‐Strobos, Nisha; Zakaria, Sammy
Abstract: Purpose: "Attending rotations" on intensive care unit (ICU) services have been in place in most teaching hospitals for decades. However, the ideal frequency of patient care handoffs is unknown. Frequent attending physician handoffs could result in delays in care and other complications, while too few handoffs can lead to provider burnout and exhaustion. Therefore, we sought to determine the correlation between frequency of attending shifts with ICU charges, 30‐day readmission rates, and mortality rates. Methods: We performed a retrospective cohort study at a large, urban, academic community hospital in Baltimore, MD. We included patients admitted into the cardiac or medical ICUs between September 1, 2012, and December 10, 2015. We tracked the number of attending shifts for each patient and correlated shifts with financial outcomes as a primary measure. Results: For any given ICU length of stay, we found no distinct association between handoff frequency and charges, 30‐day readmission rates, or mortality rates. Conclusions: Despite frequent handoffs in care, there was no objective evidence of care compromise or differences in cost. Further validation of these observations in a larger cohort is justified.